RECONSTRUCTIVE TECHNOLOGIES OF SPATIAL ORGANIZATION OF ECONOMIC SYSTEMS AND ASSESSMENT OF THE QUALITY OF THEIR SPATIAL DEVELOPMENT - В. В. Микитенко; М. О. Чупріна (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
The article defines and details fifteen quality factors of the spatial development of economic systems, which take into account the modern conditions of the functioning of the socio-economic system, challenges, risks, and threats associated with the state's ownership of natural resources, and efforts to develop the national natural resource asset. This became the basis for the development of a universal model for evaluating the quality of the spatial development of economic systems based on a generalized integral indicator as a single evaluation criterion. It is formalized according to: a) twelve integral indicators of the most important qualitative factors of spatial development (economic development; infrastructure; social development; innovativeness; environmental sustainability; tourism and cultural development; regional cooperation; digital technologies and innovations; inclusive development; water and land resources management; agrarian policy; energy security); b) taking into account the weighting coefficients for each potential factor determinant, which are defined and established by the method of logical design. Revealed and characterized: 1) the place and role of national natural resource assets in the formation of renewed economic relations in fourteen areas of sustainable management (economic, business internationalization, tax, trade, technological, infrastructural, energy, political, innovative, environmental, security, regulatory, social, geopolitical); 2) structured format, according to the importance for economic relations, the place and role of natural resource assets in the formation of renewed economic relations according to three priorities at the level of territorial formation (economic, technological, ecological) and the national level (economic, social, ecological); 3) the essence and content of reconstructive spatial technologies of the organization and development of economic systems, which made it possible to form two sets of reconstructive technologies recommended for use in Ukraine at the post-war stage of spatial organization and development of economic systems.